Exploration of collagen cavitation based on peptide electrolysis - Rui Zhai (Nature Portfolio, 2021)
Abstract Electrochemical modification of animal skin is a new material preparation method and new direction of research exploration. In this study, under the action of the electric field using NaCl as the supporting electrolyte, the effect of electrolysis on Glycyl-glycine(GlyGl), gelatin(Gel) and Three-dimensional rawhide collagen(3DC) were determined. The amino group of GlyGl is quickly eliminated within the anode region by electrolysis isolated by an anion exchange membrane. Using the same method, it was found that the molecular weight of Gel and the isoelectric point of the Gel decreased, and the viscosity and transparency of the Gel solution obviously changed. The electrolytic dissolution and structural changes of 3DC were further investigated. The results of TOC and TN showed that the organic matter in 3DC was dissolved by electrolysis, and the tissue cavitation was obvious. A new approach for the preparation of collagen-based multi-pore biomaterials by electrochemical method was explored.